An Analysis of Language Style Spoken by Mirabel in Encanto Movie - Rahmawati, Ambar; Pradana, Ami; Putra, Dhanu Ario (Jurnal Penelitian Multidisiplin Bangsa, 2026)
In this research, the researcher examines one branch of sociolinguistics, specifically language style. The focus of the research is the language style used by the character Mirabel in the movie Encanto. The primary goal of the research is to identify the language style employed by Mirabel in the Encanto movie. The researcher employs a descriptive qualitative to provide a clear and detailed explaination through written words. The findings reveal that Mirabel uses a total of 101 instances of language style in the movie, categorized as follows: 54 instances of consultative style, 25 instances of formal style, and 22 instances of casual style. The research also identifies three factors that influence the use of language style by Mirabel: the setting, the participants, and the topic. Based on these findings, it can be concluded that the consultative style is the most frequently used language style by Mirabel in the Encanto movie.